Pengenalan Strategi Promosi untuk Antisipasi Compulsive Buying kepada Siswa Kelas 5 SDN 1 Rejoso, Nganjuk, Jawa Timur - Naufal Hilmy Fauzan; Siti Aminah (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Promotion is one of the activities carried out during distribution with the aim of introducing products to potential consumers. Promotional activities in today's era can develop massively supported by adequate technology. The ease of access in shopping over time can lead to impulsive buying behavior if there is no filter on the products being viewed. To prevent impulsive buying behavior, understanding of consumer behavior or knowledge about economics should be provided to make shoppers more aware before making transactions. The activity conducted at SDN 1 Rejoso focuses on introducing materials to 5th-grade students, resulting in their understanding of entrepreneurship, buying and selling, and promotion.